2021
DOI: 10.1007/s00592-021-01760-4
|View full text |Cite
|
Sign up to set email alerts
|

Erythropoietin exposure of isolated pancreatic islets accelerates their revascularization after transplantation

Abstract: Aims The exposure of isolated pancreatic islets to pro-angiogenic factors prior to their transplantation represents a promising strategy to accelerate the revascularization of the grafts. It has been shown that erythropoietin (EPO), a glycoprotein regulating erythropoiesis, also induces angiogenesis. Therefore, we hypothesized that EPO exposure of isolated islets improves their posttransplant revascularization. Methods Flow cytometric, immunohistochemical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 47 publications
1
3
0
Order By: Relevance
“…It has been reported that the increment of islet capillaries by introducing the genes Pdpk1 , Bbs4 or Irs2 in IMECs could enhance ß cell function 28–30 . Recently, a study reported that exposure of isolated islets to erythropoietin accelerated the revascularisation of islet grafts within the initial phase after transplantation to the recipient mice 31 . In our study, treatment with dapagliflozin in db/db mice increased the islet capillaries, which might thus improve ß cell function.…”
Section: Discussionsupporting
confidence: 57%
“…It has been reported that the increment of islet capillaries by introducing the genes Pdpk1 , Bbs4 or Irs2 in IMECs could enhance ß cell function 28–30 . Recently, a study reported that exposure of isolated islets to erythropoietin accelerated the revascularisation of islet grafts within the initial phase after transplantation to the recipient mice 31 . In our study, treatment with dapagliflozin in db/db mice increased the islet capillaries, which might thus improve ß cell function.…”
Section: Discussionsupporting
confidence: 57%
“…Of note, these are the same three processes identified in the Enrichr analysis of the human serum proteomics results (Supplementary Table 3), further supporting the notion that verapamil may also have some immune-modulatory functions. Recently, the notion of pancreas-resident or infiltrating neutrophils has been established 16 and some of the leucocyte cell surface molecules included in the neutrophil-associated processes identified by Enrichr have previously been found to be expressed in isolated pancreatic islets and islet endothelial cells 17,18 . This makes it tempting to speculate that changes in these islet-resident cells may have contributed to this surprising signature in the islets.…”
Section: Resultsmentioning
confidence: 99%
“…2 D). This was confirmed by western blot (WB) and quantitative PCR (qPCR) results of CD31 and vascular endothelial growth factor A (VEGFA), two common indicators of tissue revascularization [ 22 ]. By performing qPCR, mRNA level of both CD31 (platelet endothelial cell adhesion molecule-1) and VEGFA was found to be significantly reduced in the ischemic hind limb tissue of mice in the KD group compared with those in the ND group (Fig.…”
Section: Resultsmentioning
confidence: 89%